Importance of extracorporeal membrane oxygenation (ECMO) in congenital heart diseases: a systematic review - Muhammad Shaheer Bin Faheem; Ahmed Ali Khan; Shamikha Cheema; Muzamil Akhtar; Danish Ali Ashraf (The Egyptian Heart Journal)
Abstract Background Congenital heart diseases (CHDs) represent a significant healthcare challenge with incidence rates of 17.9 per 1000 live births. Extracorporeal membrane oxygenation (ECMO) has become an invaluable therapeutic option providing essential aid to support both cardiac as well as pulmonary failure. Methods A systematic search was performed using PubMed, Embase, and Scopus from 2000 till date. Observational studies involving pediatric patients with CHD undergoing cardiac surgery using ECMO were included. The main outcomes were to determine short-term mortality, weaning off ECMO, complications, hospital and ICU length of stay, and indications for ECMO. Assessment of the risk of bias of included studies was done by Newcastle–Ottawa scale. Results 24 retrospective observational studies, encompassing 1,658 patients, were ultimately included in our review. The overall incidence of mortality across these studies was 45.2%. Successful weaning from ECMO was achieved in 73.9% of patients. The most frequently reported complications included bleeding, which affected 42.9% of patients, renal failure in 42.5%, and sepsis in 27.5%. The mean duration of hospital stay was 47.8 ± 41.1 days, while the mean length of stay in the ICU was 33.4 ± 32.6 days. Conclusions ECMO benefits pediatric heart patients but comes with risks like bleeding and high mortality. Percutaneous techniques can reduce complications; more research on minimally invasive approaches is needed.